2015
DOI: 10.1007/s13193-015-0461-5
|View full text |Cite
|
Sign up to set email alerts
|

Level IIb Neck Dissection in Oral Cavity Cancers- When Should One Address it..?

Abstract: Nodal metastases is the most important prognostic marker for oral cavity cancers. Nodal dissection at level IIb risks damage to the spinal accessory nerve. We aim to study positivity of level IIb lymph nodes in oral cancers. In this non-randomized prospective observational study, 65 patients of oral cavity cancers were evaluated. Appropriate surgery for primary tumour and neck dissection were undertaken. All patients underwent level II b dissection. Out of 67 neck dissections (27 elective and 40 therapeutic), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…It is predictable that leaving Level IIB dissected will result in a minimum amount of degenerative effect on the SAN as well as minimizes the operative time. 17 Of the 208 necks taken up for surgery irrespective of clinical N stage, the overall incidence of level IIb positivity pathologically was 22 (10.5%) as 22 patient out of 182 patients (12%) revealed metastases at level IIB (p=0.001) , which was comparable with study by Dabholkar et al 18 who gave an incidence of level IIB metastases as 10.44% and Maher et al 19 in their study had level IIB incidence of 14.5%. However, de Vicente JC et al 1 found metastasis to Level IIB as 1.8%.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It is predictable that leaving Level IIB dissected will result in a minimum amount of degenerative effect on the SAN as well as minimizes the operative time. 17 Of the 208 necks taken up for surgery irrespective of clinical N stage, the overall incidence of level IIb positivity pathologically was 22 (10.5%) as 22 patient out of 182 patients (12%) revealed metastases at level IIB (p=0.001) , which was comparable with study by Dabholkar et al 18 who gave an incidence of level IIB metastases as 10.44% and Maher et al 19 in their study had level IIB incidence of 14.5%. However, de Vicente JC et al 1 found metastasis to Level IIB as 1.8%.…”
Section: Discussionsupporting
confidence: 81%
“…23 However, for a therapeutic neck dissection, level IIb clearance should always be done if there are positive lymph nodes at level IIa clinically, or intra-operatively on frozen section. 18 As it was very troublesome to find study in published English literature pertaining to Level IIb metastasis in OSCC conducted in India, it was our sincere effort, though in a small sample size to bring out an issue, which lacks in research from this particular part of world despite having majority of patients with oral carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that the primary site for level IIb metastasis has no statistical significance. 26 , 35 But many scholars strongly recommended that dissection of level IIb in patients with tongue SCC should be incorporated into the procedures. Elsheikh et al found the incidence of metastasis at level IIb in patients with primary tumors located in the tongue to be 22%.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this region may be preserved in elective SOHND in patients with squamous cell carcinoma of the oral cavity. Dabholkar and Kapre[19] carried out a nonrandomized prospective observational study where 65 patients of oral cavity cancers were evaluated. All patients underwent Level IIb dissection.…”
Section: Discussionmentioning
confidence: 99%